The Brazil Current quasi-stationary unstable meanders at 22°S–23°S. (January 2023) - Silveira, Ilson C.A. da; Pereira, Filipe; Flierl, Glenn R.; Simoes-Sousa, Iury T.; Palóczy, André; Borges-Silva, Milton; Rocha, César B.
Abstract: The most conspicuous oceanographic features off Southeast Brazil are the quasi-stationary eddies formed off Capes São Tomé (CSTE) and Frio (CFE) associated with the Brazil Current (BC). We use SST and SSH products to infer eddy growth rates. These two independent data sets reveal an average growth rate of 0.06 day -1, and propagation speeds are virtually null. CFE tends to be more unstable and frequent than CSTE (3.5 vs. 2.3 events per year). CSTE can propagate toward the north or south while CFE only propagates southward. We perform potential vorticity (PV) inversion calculation using hydrographic data to understand how the meander growth occurs in the baroclinic jet formed by the BC and the Intermediate Western Boundary Current (IWBC). PV anomalies in one layer enhanced the anomalies on the other. This result offered in situ evidence of baroclinic conversion occurring during the eddy event captured in the observations. We then build a theoretical two-layer model calibrated with the observations seeking to explain why the eddies grow in place, and no accompanying unstable anticyclones are formed. The experiments lead us to conclude that the eddies' quasi-stationarity is due to the almost pure baroclinic nature of the BC-IWBC jet. We also find that the western boundary inhibits the formation of the anticyclones. As observed in satellite imagery, the meanders develop as isolated disturbances that may grow simultaneously or not. Highlights: Cape Frio eddies are more unstable and frequent than Cape São Tomé eddies. Eddies off Cape São Tomé propagate north and south, but Cape Frio ones only south. Unprecedented observational evidence of baroclinic growth in the meanders. Eddies' quasi-stationarity is due to the almost pure baroclinic nature of the jet. The western boundary leads to independent growth of perturbations in each cape.